Palladium‐Catalysed Decarboxylative Generation and Regiodivergent Prenylation of 2‐Azaallyl Anions. Issue 16 (5th July 2019) - Wang, Xiaoqian; Zeng, Xi; Lin, Qiao; Li, Minyan; Walsh, Patrick J.; Chruma, Jason J.
Abstract: Reaction conditions for the palladium‐catalysed decarboxylative generation and regiodivergent prenylation of 2‐azaallyl anions to form either the branched or linear prenylated benzylic imines from prenyl 2, 2‐diphenyl‐glycinate imines are reported. For certain substrates, formation of side products arising from a competitive elimination/protonation pathway could be reduced by the addition of various basic additives. The optimal basic additive and reaction concentration were found to be highly substrate dependent. Geranyl esters also proved to be viable substrates for the corresponding regiodivergent decarboxylative geranylation reactions. Preliminary efforts toward an enantioselective variant are also presented. Abstract :